Erythrocyte - Tombak, Anil (IntechOpen, 2019)
Red blood cells constitute approximately 40% of the total amount of blood and 99% of shaped elements of blood. Their major function is oxygen transportation and this makes erythrocytes "the basis of life." However, as readers will see in this book, erythrocytes have a lot of different, important functions in our body. With this book, it is planned to collect current information related to "erythrocytes." The book has been divided into two sections. The first section includes information about the roles of erythrocytes in the physiological and pathophysiological processes. The second section includes information on the future perspectives of erythrocytes like their therapeutic applications in medicine. This book will be a stepping stone for scientists who are rapidly advancing their science journey.